2016
DOI: 10.2754/avb201685010049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic zinc supplementation in weaned calves

Abstract: The aim of the study was to investigate the effect of organic zinc supplementation in calves on serum zinc (Zn) concentrations, selected metabolic profile indicators and serum immunoglobulin (Ig) concentrations. The trial included 2 groups (n = 10) of weaned female calves. The Zn-Methionin calves (group Zn-Met) were supplemented with 30 mg Zn-Met/kg dry matter (DM)/day (BIOPLEX ® Zn, Alltech, USA) for 90 days; the control calves (group C) received the same diet without organic zinc supplementation. Compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
2
15
0
1
Order By: Relevance
“…Oxidative stress happens when the excessive production of reactive oxygen species overwhelms the capacity of antioxidant systems in the body (27,28). Previous studies have shown that zinc has an antioxidant function (29), and supplementation with ZM reportedly decreases the concentration of MDA, but increases that of MT and T-AOC in the serum of ruminants (14,17,23), and similar results were also observed in the present study. Different from ZM, ZP did not present the same antioxidant effects as ZM because it did not affect the serum MT or T-AOC concentrations compared with the CON group.…”
Section: Discussionsupporting
confidence: 91%
“…Oxidative stress happens when the excessive production of reactive oxygen species overwhelms the capacity of antioxidant systems in the body (27,28). Previous studies have shown that zinc has an antioxidant function (29), and supplementation with ZM reportedly decreases the concentration of MDA, but increases that of MT and T-AOC in the serum of ruminants (14,17,23), and similar results were also observed in the present study. Different from ZM, ZP did not present the same antioxidant effects as ZM because it did not affect the serum MT or T-AOC concentrations compared with the CON group.…”
Section: Discussionsupporting
confidence: 91%
“…In comparable with the recent results of Zn-Me supplementation in different species, Mostafa et al (2019) found significant increase in TP and AL in She-camel. Also, serum TP and AL concentrations showed significant increase in dairy calves (Dresler et al, 2016). Plasma TP increased with Zn dietary supplementation in broiler (Bahakaim et al, 2014).…”
Section: Blood Biochemicalsmentioning
confidence: 83%
“…However, some extent of dissociation and loss of organic trace minerals in the upper gastro-intestinal tract is unavoidable (Cao et al 2000). Despite these inevitable losses, organic trace mineral supplementation can benefit the nutrition of ruminants, improving their production and health (Gressley 2009;Dresler et al 2016).…”
Section: Discussionmentioning
confidence: 99%